Systems thinking and e-participation : ICT in the governance of society - Cordoba-Pachon, Jose-Rodrigo.; Ochoa-Arias, Alejandro (Hershey [PA] : Information Science Reference, 2010)
'This book provides a systemic-based inquiry platform to explore boundaries, limits, and advantages of information and communication technology use in the public decision making processes'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 310-337) and index.
Keywords: Internet in public administration -- Cross-cultural studies; Political participation -- Computer networks -- Cross-cultural studies; Communication in politics